SseK1 and SseK3 T3SS effectors inhibit NF-kB signalling and necroptotic cell death in Salmonella-infected macrophages - Gunster,R; Matthews,SA; Holden,DW; Thurston,T (Infection and Immunity, 2017)
Within host cells such as macrophages, Salmonella enterica translocates virulence (effector) proteins across its vacuolar membrane using the SPI-2 type III secretion system. Previously it has been shown that when expressed ectopically the effectors SseK1 and SseK3 inhibit TNFα-induced NF-κB activation. In this study we show that ectopically expressed SseK1, SseK2 and SseK3 suppressed TNFα-, but not TLR4-, or interleukin-induced NF-κB activation. Inhibition required a DXD motif, which in SseK1 and SseK3 is essential for protein Arginine-N-acetylglucosamine (GlcNAc)-ylation. During macrophage infection, SseK1 and SseK3 inhibited NF-κB activity in an additive manner. SseK3-mediated inhibition of NF-κB activation did not require the only known host-binding partner of this effector, the E3-ubiquitin ligase TRIM32. SseK proteins also inhibited TNFα-induced cell death during macrophage infection. Despite SseK1 and SseK3 inhibiting TNFα-induced apoptosis upon ectopic expression in HeLa cells, the percentage of infected macrophages undergoing apoptosis was SseK-independent. Instead, SseK proteins inhibited necroptotic cell death during macrophage infection. SseK1 and SseK3 caused GlcNAcylation of different proteins in infected macrophages suggesting that these effectors have distinct substrate specificities. Indeed, SseK1 caused the GlcNAcylation of the death domain containing proteins FADD and TRADD, whereas SseK3 expression resulted in weak GlcNAcylation of TRADD but not FADD. Additional, as yet unidentified substrates are likely to explain the additive phenotype of a Salmonella strain lacking both SseK1 and SseK3.